Reducing Five Finger Hypnotic Therapy on the Anxiety Level of Communities Affected by Phoneing - Islahiyah Pratiwi; Rina Anggraeni; Livana PH; Mohammad Fatkhul Mubin (Proceedings of the International Conference on Nursing and Health Sciences, 2022)
The COVID-19 pandemic attacks the human respiratory system because of its very rapid development, so the government implements the PSBB policy. So that some companies cannot supply raw materials and suffer losses due to decreased sales, causing several employees to be laid off or lose their jobs and cause psychological problems for fear of not being able to fulfill their daily lives. To reduce anxiety psychological problems with various therapies, one of which is five finger therapy. The research used Quasy experiment with pretest posttest with one group design, the type of quantitative research. The research sample amounted to 29 respondents with total sampling therapy. The results of data analysis showed that the majority of early adulthood were 23 years old, female 15 and male 14. High school education was 24, majority marital status was unmarried amounted to 23. The level of anxiety of respondents before being given five-finger therapy was majority at moderate anxiety level of 21. After being given five-finger therapy, the majority had no anxiety with a result of 19.